A Biochemical Approach for Hedysarum candidissimum from Turkey: Screening Phytochemicals, Evaluation of Biological Activites, and Molecular Docking Study. Issue 9 (31st August 2022) - Altay, Ahmet; Yeniceri, Esma; Taslimi, Parham; Taskin‐Tok, Tugba; Yilmaz, Mustafa Abdullah; Koksal, Ekrem
Abstract: This study was designed to screen the phytochemical composition and investigate the biological activities of Hedysarum candidissimum extracts and also support the results with molecular docking studies. LC/MS/MS analysis revealed the presence of 22 phytochemical constituents (mainly phenolic acids, flavonoids, and flavonoid glycosides) in the plant structure. The methanol extract exhibited the strongest antioxidant activity among all the extracts with its strong DPPH radical scavenging and iron reducing capacity, as well as high phenolic and flavonoid contents. Additionally, it was found to be the most promising acetylcholinesterase (AChE: IC50 : 93.26 μg/mL) and α‐glycosidase (AG: IC50 : 28.57 μg/mL) inhibitory activities, supported by the major phenolics of the species through in silico studies. Ethyl acetate extract had the strongest cytotoxic effect on HT‐29 (IC50 : 63.03 μg/mL) and MDA‐MB‐453 (IC50 : 95.36 μg/mL) cancer cell lines. Both extracts exhibited considerable apoptotic and anti‐migrative effects on HT‐29 cells. The investigations provide phyto‐analytical and bio‐pharmacological results which can be extended by in vivo studies in the future. Abstract :